Geochemical and Hf isotopic compositions of Late Triassic–Early Jurassic intrusions of the Erguna Block, Northeast China: petrogenesis and tectonic implications. Issue 3 (17th February 2017) - Gou, Jun; Sun, De-You; Ren, Yun-Sheng; Hou, Xue-Gang; Yang, Dong-Guang
ABSTRACT: Late Triassic–Early Jurassic intrusions of the Erguna Block, Northeast China, are located along the southern margin of the Mongol–Okhotsk orogenic belt. They comprise granodiorite, monzogranite, syenogranite, and lesser gabbro–diorite, of adakitic and calcalkaline affinity. The adakite-like and calcalkaline granites share similar light rare earth elements (LREE) characteristics; however, their heavy rare earth elements (HREE) trends differ from one another. The relative abundances of HREE in the calcalkaline granites are relatively consistent and are similar to those of intrusive rocks formed from dehydration melting of garnet-free amphibolitic source rocks at relatively low pressures. In contrast, the adakite-like granites show more prominent HREE fractionation trends, indicating that they crystallized at higher pressures, where garnet in the source rocks was stable. At least two isotopically distinct sources were involved in the petrogenesis of the granites, but the extent to which they contributed varies between plutons. Most intrusions have incorporated an isotopically primitive component, possibly juvenile mafic crust. The other sources include a small proportion of old continental crustal material and isotopically evolved wall rocks. The gabbro–diorites have high MgO contents (>7 wt.%), a high Mg # (>0.6), and show moderate LREE and HREE fractionation, indicating they formed from the melting of subducted metasomatized lithospheric mantle. All of the intrusions in the study area are characterized by a relative enrichment in large ion lithophile elements (LILE) and depletion in high field strength elements (HFSE), indicating they were emplaced in an Andean-type active continental margin setting related to southward subduction of the Mongol–Okhotsk oceanic plate.